PENGARUH PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI, DAN BUDAYA ORGANISASI PADA SENJANGAN ANGGARAN DI KOPERASI KOTA MALANG - Eva Suhrotur Rohmah; Moh. Amin; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the effect of budgeting participation, information asymmetry, and organizational culture on budgetary slack in Malang cooperative. The population in this study is cooperatives in the city of Malang. The sample used is part of the Malang city cooperative with the respondents are managers, members and administrators who participated in the cooperative budgeting process in Malang City. The technique used in sampling is the Purposive Sampling technique, the sample selected was 30 cooperatives. Data was taken using the questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS version 14 software (Product Statistics and Solution Services version 14). The test data used is the simultaneous hypothesis test (f), determination coefficient (R2), and partial hypothesis test (t). The results of the study indicate that simultaneously the independent variables significantly influence the dependent variable. Based on the test results of the coefficient of determination, the adjusted R value is 65.4% while the remaining 34.6% is influenced by other variables not included in this study. Based on the results of the partial test two variables have an influence on budgetary slack, budgeting participation (sig = 0.021), organizational culture (sig = 0.006) while information asymmetry (sig = 0.296) has no effect on budgetary slack. Keywords :       budgeting participation, information asymmetry, organizational culture and budgetary slack